Software Designation to Assess the Proximity of Different Facial Anatomic Landmarks to Midlines of the Mouth and Face - Moshkelgosha V; Zare R; Safari A (Journal of Dental Biomaterial, 2014)
Statement of Problem: Recognition and determination of facial and dental midline is important in dentistry. Currently, there are no verifiable guidelines that direct the choice of specific anatomic landmarks to determine the midline of the face or mouth. Objectives: The purpose of this study was to determine which of facial anatomic landmarks is closest to the midline of the face as well as that of the mouth. Materials and Methods: Frontal full-face digital images of 92 subjects (men and women age range: 20-30 years) in smile were taken under standardized conditions; commonly used anatomic landmarks, nasion, tip of the nose, and tip of the philtrum were digitized on the images of subjects and aesthetic analyzer software used for midline analysis using Esthetic Frame. Deviations from the midlines of the face and mouth were measured for the 3 clinical landmarks; the existing dental midline was considered as the fourth landmark. The entire process of midline analysis was done by a single observer and repeated twice. Reliability analysis and 1-sample t- tests were conducted. Results: The Intra-class correlation coefficients (ICCs) for reliability analysis of RFV and RCV measures made two times revealed that the reliabilities were all acceptable. The results indicated that each of the 4 landmarks deviated uniquely and significantly (P<.001) from the midlines of the face as well as mouth in both males and females. Conclusions: There was a significant difference between the mean ratios of the chosen anatomic landmarks and the midlines of the face and mouth. The hierarchy of anatomic landmarks closest to the midline of the face is: (1) midline of the commissures, (2) nasion , (3) tip of philtrum,(4 )dental midline, and (5) tip ofthe nose. The closest anatomic landmarks to the mouth midline are: (1) tip of philtrum, (2) dental midline, (3) tip of nose, and (4) nasion.